Leaf Vegetable Seed Germination in Various Concentrations of Organic Liquid Fertilizer Based on Manure - Doni Supambri; Muhammad AlQamari; Sashikala Maruthai Pillai (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
The use of liquid organic fertilizer (POC) derived from manure is an alternative nutrient source with the potential to enhance seed vigor and early plant growth. This study aimed to analyze the germination dynamics of four horticultural crops (kailan, lettuce, bok choy, and mung beans) and determine the most effective dose of a cow dung-based liquid organic fertilizer. The experiment was conducted at the MARDI Malaysia Organic Farm using a non-factorial Randomized Block Design (RBD) with six POC concentration treatments (0%, 1%, 2%, 3%, 4%, and 5%) and four replications. Observed parameters included germination rate, plant height, number of leaves, root length, fresh weight, and dry weight. Results indicated that the 3–4% POC treatment elicited the best response across most parameters. The highest germination rate was recorded at concentrations of 3–5%, ranging from 20.33% to 23.00%, while the maximum seedling height of 20.38 cm was observed at a 3% dose. The greatest root length was found in the 5% treatment, measuring 17.50 cm for kailan, followed by 9.50 cm for bok choy and 8.75 cm for lettuce. The highest fresh and dry weights, 2.38 g and 0.38 g, respectively, were recorded in mung beans at a 4% concentration. Overall, manure-based POC at a 3–4% dose proved optimal for enhancing germination dynamics and early plant growth without inducing physiological stress.